Developing an Entrepreneur's Soul Through Hadith - Ibrahim Al-Khalil; Ahmad Mohammad Tijani (Values: Jurnal Kajian Islam Multidisiplin, 2024)
This study emphasizes the importance of developing a resilient and ethical entrepreneurial spirit through the guidance of the hadiths of Prophet Muhammad (PBUH). In the context of the globalized era, entrepreneurship has become one of the key drivers in promoting economic growth. Islam provides profound guidance in spiritual and moral aspects, particularly concerning trade, work ethic, and innovation. Hadiths related to entrepreneurship, such as the virtues of trade and the importance of lawful business practices, serve as motivation and guidance for Muslims in conducting business in accordance with Islamic values. Although some hadiths on trade are considered weak by scholars, this study finds that they still serve as a source of inspiration in shaping entrepreneurs with integrity. Values such as hard work, honesty, and the reward for lawful efforts are emphasized in these hadiths. Therefore, Muslim entrepreneurs are expected to run businesses that are blessed, sustainable, and beneficial to society, based on Islamic principles